Caregiver Experiences and Roles in Care Seeking During COPD Exacerbations: A Qualitative Study. Issue 3 (24th June 2021) - Suresh, Madhuvanthi; Young, Jessica; Fan, Vincent; Simons, Carol; Battaglia, Catherine; Simpson, Tracy L; Fortney, John C; Locke, Emily R; Trivedi, Ranak
Abstract: Background: Chronic obstructive pulmonary disease (COPD) is a progressive, debilitating illness characterized by exacerbations that require timely intervention. COPD patients often rely on informal caregivers—relatives or friends—for assistance with functioning and support. Caregivers perform roles that may be particularly important during acute exacerbations in monitoring symptoms and seeking medical intervention. However, little is known about caregivers' roles and experiences as they support their patients during exacerbations. Purpose: To explore the experiences, roles in care seeking, and needs of caregivers during COPD exacerbations. Methods: Semi-structured interviews were conducted with 24 caregivers of Veterans with COPD who experienced a recent exacerbation. Interviews were recorded, transcribed, and analyzed using inductive content analysis. Results: Five themes arose: (a) caregivers reported continuously monitoring changes in patients symptom severity to identify exacerbations; (b) caregivers described emotional reactions evoked by exacerbations and constant vigilance; (c) caregivers described disagreements with their patient in interpreting symptoms and determining the need for care seeking; (d) caregivers noted uncertainty regarding their roles and responsibilities in pursuing care and their approaches to promote care varied; and (e) expressed their need for additional information and support. Caregivers of patients with COPD often influence whether and when patients seek care during exacerbations. Discrepancies in symptom evaluations between patients and caregivers paired with the lack of information and support available to caregivers are related to delays in care seeking. Clinical practice should foster self-management support to patient–caregiver dyads to increase caregiver confidence and patient openness to their input during exacerbations. Abstract : Caregivers of chronic obstructive pulmonary disease (COPD) patients report challenges with COPD self-management and anxiety related to care seeking during acute exacerbations, and desire additional support and information